Pengaruh Kegagalan Keuangan terhadap Nilai Pasar Perusahaan-Perusahaan Retail Indonesia Yang Terdaftar di Bursa Efek Indonesia - Iis Kurniasari; Tantri Yanuar Rahmat Syah (Owner : Riset dan Jurnal Akuntansi, 2022)
The development of e-commerce in Indonesia became a factor that threatened retail businesses, even some of them went bankrupt due to liquidation that led to financial failure. Financial failure is not detected within a certain time so it is likely that the company will go bankrupt. This study aims to determine the effect of financial distress on the market value of Indonesian retail companies listed on the Indonesia Stock Exchange. The study was conducted quantitatively. The study was conducted on 17 retail companies in Indonesia on the Indonesia Stock Exchange which published their audited financial statements for 3 consecutive years, namely 2016-2018. The sampling technique used was purposive sampling. The independent variable is financial failure measured by using the Altman Z-score and the dependent variable is market value. Data were analyzed by linear regression panel data with fixed effect method. The results show that the Altman model can be used to measure signs of corporate financial distress. Most of the 2016-2018 IDX retail companies are not vulnerable to financial distress and are in a healthy financial situation. Financial distress is stated to have a significant and positive effect on the market value of BEI retail industry companies in 2016-2018.